2008
DOI: 10.1194/jlr.m800167-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Phase composition of lipoprotein SM/cholesterol/PtdCho affects FA specificity of sPLA2s

Abstract: We have previously reported preferential release of polyunsaturated FAs during hydrolysis of lipoprotein phosphatidylcholine (PtdCho) by group X secretory phospholipase A 2 (sPLA 2 ) and preferential release of oligounsaturated FAs during hydrolysis of lipoprotein PtdCho by group V sPLA 2 , but the mechanism of this selectivity has remained unknown. We now show that the rate and specificity of hydrolysis are affected by relative increases in endogenous SM and free cholesterol (FC) during the lipase digestion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
(74 reference statements)
2
9
0
Order By: Relevance
“…We previously demonstrated that the main mediators of parasite death by bee venom sPLA 2 -hydrolyzed VLDLs are PUFAs, especially AA, suggesting that the ability to produce PUFAs might be an important feature of the sPLA 2 anti-Plasmodium activity. It is known that hGX sPLA 2 preferentially hydrolyzes PC with polyenoic fatty acid species, including AA (41,42,(46)(47)(48), and that hGIIF sPLA 2 exhibits preference for PC species with AA (44), whereas hGV sPLA 2 preferentially attacks oligoenoic PL species and mostly releases saturated and monounsaturated fatty acids (41,42,(46)(47)(48). hGIII sPLA 2 did not seem to exhibit any PL preference (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that the main mediators of parasite death by bee venom sPLA 2 -hydrolyzed VLDLs are PUFAs, especially AA, suggesting that the ability to produce PUFAs might be an important feature of the sPLA 2 anti-Plasmodium activity. It is known that hGX sPLA 2 preferentially hydrolyzes PC with polyenoic fatty acid species, including AA (41,42,(46)(47)(48), and that hGIIF sPLA 2 exhibits preference for PC species with AA (44), whereas hGV sPLA 2 preferentially attacks oligoenoic PL species and mostly releases saturated and monounsaturated fatty acids (41,42,(46)(47)(48). hGIII sPLA 2 did not seem to exhibit any PL preference (44).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was also supported by studies showing that human sPLA 2 s exhibit different selectivities toward lipoprotein-PC species with different fatty acids at the sn-2 position. Indeed, it was shown that hGX sPLA 2 preferentially hydrolyzes PC with linoleic acid (LA; 18:2) and arachidonic acid (20:4) at the sn-2 position, whereas hGV sPLA 2 prefers PC with LA and oleic acid (OA; 18:1) (41,44,46,47). Furthermore, hGIII exhibited no preference toward PC species from LDL and HDL, whereas hGIIF sPLA 2 attacks PC species with AA preferentially (44).…”
Section: Falciparum-infectedmentioning
confidence: 99%
“…Nevertheless, GV and GX sPLA 2 have been shown to be quite potent in mobilizing arachidonic acid and stimulating eicosanoid synthesis in various cell types [51,52], and thus may play an important role in inflammation and inflammatory diseases, as discussed in more detail in a subsequent section of this review. Interestingly, membrane sphingomyelin/ceramide content has been shown to modulate both the activity and arachidonic acid selectivity of GV and GX sPLA 2 [46,[53][54][55], suggesting a novel mechanism whereby sphingolipids may regulate sPLA 2 -induced inflammatory responses. The exact mechanism by which sphingomyelin/ceramide modulates sPLA 2 activity is not clearly understood, although the change in fatty acid specificity has been attributed to segregation of PC and sPLA 2 between disordered and ordered sphingomyelin/free cholesterol/PC lipid phases [53].…”
Section: Biochemical Propertiesmentioning
confidence: 98%
“…Interestingly, membrane sphingomyelin/ceramide content has been shown to modulate both the activity and arachidonic acid selectivity of GV and GX sPLA 2 [46,[53][54][55], suggesting a novel mechanism whereby sphingolipids may regulate sPLA 2 -induced inflammatory responses. The exact mechanism by which sphingomyelin/ceramide modulates sPLA 2 activity is not clearly understood, although the change in fatty acid specificity has been attributed to segregation of PC and sPLA 2 between disordered and ordered sphingomyelin/free cholesterol/PC lipid phases [53].…”
Section: Biochemical Propertiesmentioning
confidence: 98%
“…Secondly, lipoprotein phospholipid (PL) content is altered in apoE -/- mice, such that the SM to PC ratio is relatively high due to increased SM production and decreased SM degradation13. Since previous in vitro data demonstrate that GV sPLA 2 hydrolysis of PC in liposomes and human LDL is inhibited by SM 6, 14-16, we speculated that particles from apoE -/- mice may be relatively poor substrates for GV sPLA 2 hydrolysis.…”
Section: Introductionmentioning
confidence: 99%